Hydrolysis of insoluble fish protein residue from whitemouth croaker (Micropogonias furnieri) by fungi - Vilásia Guimarães Martins; Simone Canabarro Palezi; Jorge Alberto Vieira Costa; Carlos Prentice (Brazilian Archives of Biology and Technology, 2014)
A significant amount of insoluble fibrous protein, in the form of feather, hair, scales, skin and others are available as co-products of agro industrial processing. These wastes are rich in keratin and collagen. This study evaluated different fungi for the hydrolysis of insoluble fish protein residues. Proteins resulting from Micropogonias furnieri wastes through pH-shifting process were dried and milled for fermentation for 96 h. This resulted the production of keratinolytic enzymes in the medium. Trichoderma sp. on alkaline substrate (28.99 U mL-1) and Penicillium sp. on acidic substrate (31.20 U mL-1) showed the highest proteolytic activities. Penicillium sp. showed the largest free amino acid solubilization (0.146 mg mL-1) and Fusarium sp. the highest protein solubilization (6.17 mg mL-1).